P5 Penerapan P5 (projek penguatan profil pelajar pancasila) dalam mengembangkan kualitas pembelajaran di Sekolah Dasar Negeri Halimaneek Kabupaten Malaka - Klau, Djefridus (IKIP Siliwangi, 2025)
Abstract This research is motivated by the need to improve the quality of education in remote areas such as Malaka Regency. The importance of this research lies in the effort to understand how the Independent Curriculum, especially P5, can be implemented. The purpose of this study is to analyze and measure the achievement of learning quality at the elementary school level in Malaka Regency in implementing the Independent Curriculum, especially in the implementation of P5. The method used in this study is a descriptive qualitative method with data collection techniques through a semi-structured questionnaire or interview questionnaire. This research was conducted at Halimaneek Elementary School, Rinhat District, Malaka Regency. The respondents used were 4 teachers. The results of the study showed that the implementation of P5 with the theme of Local Wisdom with vegetable planting activities not only increased students' knowledge of agriculture but also built their character in working together or collaborating and being responsible. This is evidenced by students becoming more enthusiastic in learning when they are directly involved in practical activities. The implementation of the Independent Curriculum is manifested in the dimensions of the Pancasila student profile who believe in and are devoted to God Almighty and have noble morals, are independent and work together. can develop the quality of elementary school learning in Malaka Regency. Thus, this study can explore the challenges of teachers in implementing the Merdeka Curriculum and the project-based P5 model can increase student engagement and its impact on understanding science and environmental concepts through vegetable planting activities to realize the dimensions of the Pancasila student profile with quality learning in elementary schools in Malaka Regency. Especially Halimaneek State Elementary School. Keywords: Learning Quality, Pancasila Student Profile Strengthening Project, Elementary School. Abstrak Penelitian ini dilatarbelakangi oleh kebutuhan untuk meningkatkan kualitas pendidikan di daerah terpencil seperti Kabupaten Malaka. Pentingnya penelitian ini terletak pada upaya untuk memahami bagaimana Kurikulum Merdeka khususnya P5 dapat diterapkan. Tujuan penelitian ini adalah untuk menganalisis dan mengukur ketercapaian kualitas pembelajaran pada jenjang pendidikan SD di Kabupaten Malaka dalam menerapkan Kurikulum Merdeka khususnya dalam pelaksanaan P5. Metode yang digunakan dalam penelitian ini adalah metode kualitatif deskriptif dengan teknik pengumpulan data melalui teknik angket atau kuesioner wawancara yang bersifat semi-terstruktur. Penelitian ini dilakukan di SD Negeri Halimaneek Kecamatan Rinhat Kabupaten Malaka. Responden yang digunakan adalah 4 guru. Hasil penelitian menunjukkan bahwa penerapan P5 dengan tema Kearifan Lokal dengan kegiatan menanam sayur tidak hanya meningkatkan pengetahuan siswa tentang pertanian tetapi juga membangun karakter mereka dalam bekerja sama atau kolaborasi dan bertanggung jawab. Hal ini dibuktikan dengan siswa menjadi lebih antusias dalam belajar ketika mereka terlibat langsung dalam kegiatan praktis. Penerapan Kurikulum Merdeka terwujud dalam dimensi profil pelajar pancasila yang beriman dan bertaqwa Kepada Tuhan Yang Maha Esa dan berakhlak Mulia, mandiri dan gotong royong. dapat mengembangkan kualitas pembelajaran SD di Kabupaten Malaka. Dengan demikian, penelitian ini dapat mengeksplorasi tantangan guru dalam menerapkan Kurikulum Merdeka serta model P5 yang berbasis proyek dapat meningkatkan keterlibatan siswa dan dampaknya terhadap pemahaman konsep sains serta lingkungan melalui kegiatan menanam sayur terwujud dimensi profil pelajar pancasila dengan pembelajaran berkualitas SD Di Kabupaten Malaka. Khususnya SD Negeri Halimaneek. Kata Kunci: Kualitas Pembelajaran, Projek Penguatan Profil Pelajar Pancasila, Sekolah Dasar.